Stability and stabilizability of a class of uncertain dynamical systems with delays - Saadni, Mohammed Salah; Chaabane, Mohammed; Mehdi, Driss (Zielona Góra: Uniwersytet Zielonogórski)
This paper deals with a class of uncertain systems with time-varying delays and norm-bounded uncertainty. The stability and stabilizability of this class of systems are considered. Linear Matrix Inequalities (LMI) delay-dependent sufficient conditions for both stability and stabilizability and their robustness are established.
Keywords: dynamical systems; time-varying delays; time-varying uncertainty; norm-bounded robust stability; robust stabilizability